Alexander in Jerusalem: Scribal Innovation and Biblical Propaganda in Kyivan Rus - Torres Prieto, Susana (Institute of Archaeology, Czech Academy of Sciences, 2022)
Alexander of Macedon’s life as narrated in the Alexander Romance was inserted early in historiographic works in East Slavic. One of the most innovative details was the inclusion of the visit to Jerusalem of Alexander of Macedon in the First Book, following the wording found in the chronicle of George Hamartolos, an episode he had borrowed from Josephus. More surprising was the later interpolation within this interpolation of a part of Epiphanios of Salamis’ treatise De Gemmis, precisely the part describing the robes of the high priest in the Jewish temple and its relation to the filiation of the tribes of Israel. Neither addition was accidental, and their resonances echoed loudly in the limited literary corpus in Kyivan Rus’ dealing with sacred kingship. The present article explores the functionality and instrumental use made by Kyivan scribes of the figure of the Macedonian king and his special relation to the chosen people of God. It was by means of these additions that Alexander acquired exclusively in East Slavic the special status of a king whose deeds are key in the salvation of Israel and of all Christianity.
Keywords: Alexander of Macedon; limited literary corpus; De Gemmis; Israel; Macedon; East Slavic; George Hamartolos; Jewish Temple; 62 Ciencias de las Artes y las Letras; ODS 4 - Educación de calidad